Listening to Students: Voices From the Inner City - Bean, Rita M.; Eichelberger, R. Tont; Lazar, Meryl; Morris, Gregory A.; Reed, Cindy A. (Catholic Education: A Journal of Inquiry and Practice, 2000)
What do students in Catholic schools view as important aspects of their unique form of education? They want a safe environment for learning, caring and concerned teachers, high expectations for learning, responsibility and respect in the school community, and a clear sense of how school relates to success in life. This article describes a study which clearly documents student perceptions and values.